Evaluation of in vitro antioxidant activity and HPTLC finger printing analysis of Physalis peruviana fruits (International Journal of Pharmaceutical Sciences and Drug Research, 2020)
In this research work to evaluate in vitro antioxidant activity and HPTLC finger printing analysis of Physalis peruviana fruits. The chemical fingerprinting was carried out by high performance thin layer chromatography. It was carried out by the CAMAG HPTLC system equipped with Linomat V sample applicator, twin through plate development chamber, TLC scanner III and integration software WIN CATS-4.02. Physalis peruviana fruit extract was tested for phytochemical screening and in vitro anti-oxidant enzymes like 2, 2-diphenyl-1-picryl hydrazyl radical (DPPH), total antioxidant activity and reducing ability. Physalis peruviana fruit extract effectively scavenged free radicals at all different concentrations and showed its potent antioxidant activity. Phytochemical analysis revealed the presence of various major phytoconstituents like alkaloids, flavonoids, saponins, phenolics, tannins and anthraquinones. The HPTLC fingerprint qualitatively revealed predominant amount of quercetin. Physalis peruviana fruit extract will be subjected to further extensive studies to isolate and identify their active constituents which are useful for understanding their mechanism of action as antioxidants.